2014
DOI: 10.1007/978-3-319-11731-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the Hsp90-Binding FKBP Immunophilins

Abstract: Hsp90 functionally interacts with a broad array of client proteins, but in every case examined Hsp90 is accompanied by one or more co-chaperones. One class of co-chaperone contains a tetratricopeptide repeat domain that targets the co-chaperone to the C-terminal region of Hsp90. Within this class are Hsp90-binding peptidylprolyl isomerases, most of which belong to the FK506-binding protein (FKBP) family. Despite the common association of FKBP co-chaperones with Hsp90, it is now clear that the client protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 203 publications
1
27
0
Order By: Relevance
“…Thus, whether FKBP10 serves as tumor suppressor or oncogene depends on the different tissues. Although, we did not investigate the exact mechanisms by which FKBP10 regulates cellular phenotypic changes, previous studies suggested that HSP90 had close relation with FKBP10 [26,27] . HSP90 has emerged as a molecular target for cancer therapeutics and HSP90 inhibitors can inhibit multiple signaling pathways on which cancer cells depend for growth and survival [28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, whether FKBP10 serves as tumor suppressor or oncogene depends on the different tissues. Although, we did not investigate the exact mechanisms by which FKBP10 regulates cellular phenotypic changes, previous studies suggested that HSP90 had close relation with FKBP10 [26,27] . HSP90 has emerged as a molecular target for cancer therapeutics and HSP90 inhibitors can inhibit multiple signaling pathways on which cancer cells depend for growth and survival [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Most FKBPs can interact with the C-terminal region of HSP90 to influence a broad array of proteins in signal transduction [19] . Different from all the other family proteins, FKBP10 contains 4 PPIase domains [20,21] . FKBP10 has been implicated in ovarian cancer [17,22] , colorectal cancer [23] , KRAS-induced lung cancer [18] , prostate cancer [24], and leukemia [25] .…”
Section: Introductionmentioning
confidence: 99%
“…Both are also ubiquitous proteins with highly conserved sequence. The binding exhibits various degrees of specificity between the two partners; Hsp90, for example, is preferred over Hsp70 to bind to the TPRs of the large FKBPs (Assimon et al 2015;Guy et al 2015). In particular, peptide-TPR co-crystal structure and mutational analysis have established that the invariant C-terminal pentapeptide, MEEVD, of Hsp90 (Gupta 1995) interacts with specific residues that are common to the TPRs of long FKBPs and CYNs (Assimon et al 2015;Cliff et al 2006;Scheufler et al 2000;Ward et al 2002;Wu et al 2004).…”
Section: Gammaproteobacteriamentioning
confidence: 99%
“…Hsp90 plays a central role in many physiological processes through its substrates or client proteins. The majority of Hsp90 clients are associated with signal transduction, and include nuclear steroid hormone receptors (Guy et al, 2015) and roughly half of all kinases (Taipale et al, 2012). The upregulation of signaling clients in many cancers leads to an increased dependence on Hsp90.…”
Section: Introductionmentioning
confidence: 99%
“…The “lid” region of the ATPase domain adopts distinct nucleotide-bound conformations (Ali et al, 2006; Prodromou et al, 1997) including transient dimerization when ATP and the co-chaperone p23 are bound that in turn mediate dramatic conformational changes of the full-length Hsp90 dimer (Southworth and Agard, 2008). Purified Hsp90 can act as an anti-aggregation chaperone (Pursell et al, 2012), but activation of signaling clients including kinases and nuclear steroid receptors in vitro requires multiple co-chaperones including p23, Hop, Cdc37, and Hsp70 (Arlander et al, 2006; Boczek et al, 2015; Guy et al, 2015). Exciting recent views of Hsp90 bound to clients and co-chaperones (Karagoz et al, 2014; Kirschke et al, 2014; Vaughan et al, 2006) indicate that different clients can bind to distinct surfaces of Hsp90.…”
Section: Introductionmentioning
confidence: 99%